2013
DOI: 10.3109/13880209.2013.790064
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and matrix metalloproteinase-2 inhibition of Longkong (Lansium domesticum) extracts on human mouth epidermal carcinoma

Abstract: Context: Longkong [Lansium domesticum Corr. (Meliaceae)] is a popular tropical plant producing economic edible fruits found mainly in Southeast Asia. However, limited information is available concerning anticancer activity of Longkong. Objective: To investigate anticancer activities in human mouth epidermal carcinoma (KB) of Longkong extracts. Materials and methods: Various parts of Longkong which was collected from Northern and Eastern of Thailand were extracted by the hot and cold processes using water, chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Phytochemical screening of the bark revealed the existence of anthraquinones, alkaloids, flavonoids, coumarins, cardiac glycosides, tannins, saponins, and iridoids [ 24 ]. Further, a toxic constituent such as lansium acid (6%) was detected in the peel [ 52 , 53 ]…”
Section: Phytoconstituents Of L Domesticummentioning
confidence: 99%
See 3 more Smart Citations
“…Phytochemical screening of the bark revealed the existence of anthraquinones, alkaloids, flavonoids, coumarins, cardiac glycosides, tannins, saponins, and iridoids [ 24 ]. Further, a toxic constituent such as lansium acid (6%) was detected in the peel [ 52 , 53 ]…”
Section: Phytoconstituents Of L Domesticummentioning
confidence: 99%
“…Further, the phytochemical analysis of the ethyl acetate (LDSK50-EA) and aqueous (LDSK50-H 2 O) fractions of longkong peels illustrated the presence of phenolics, mainly chlorogenic acid ( 29 ), rutin ( 30 ), and scopoletin ( 31 ) [ 51 ]. It is noteworthy to state that the pericarp possessed a higher flavonoid content than flesh, while the seeds have no flavonoids [ 53 ]. A high flavonoids yield was observed in the fruit extracted with hot H 2 O in comparison to other kinds of solvents [ 43 ].…”
Section: Phytoconstituents Of L Domesticummentioning
confidence: 99%
See 2 more Smart Citations
“…The seeds are used as a fever remedy, the bark is used as medicine to treat scorpion sting (Tilaar et al, 2008), and the leaves are used to repel mosquitoes (Klungsupya et al, 2015). Besides that, some studies showed that L. domesticum has antimalarial (Saewan et al, 2006), antiproliferation (matrix metalloproteinase-2 inhibition on human oral epidermal carcinoma) (Manosroi et al, 2013), anti-oxidative, and analgesic activity (Apridamayanti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%